(untitled) (Hoboken, N.J., 2006)
Many researchers believe that GSK-3 and its inhibitors could lead to effective treatments for neurogenerative disorders, type II diabetes, depression and bipolar disorder, and some forms of cancer. This book provides a thorough introduction to GSK-3, presents up-to-date information, and mentions the birth of several chemical families of GSK-3 inhibitors with varying selectivity. It’s a great reference for researchers in drug design and development
Keywords: Glycogen synthase kinase-3,Glycogen synthase kinase-3,Hóa sinh học,Glycogen synthase kinase-3; Inhibitors,Chất ức chế